Analisis Fundamental dan Teknikal terhadap Return Saham pada Perusahaan Multisektor IDX 30 yang Terdaftar di BEI - Sindi Ayu Lusiana; Lukita Tripermata; Andini Utari Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the influence of fundamental and technical analysis on stock returns of multi-sector companies listed in the IDX30 index on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Fundamental analysis is measured using Return on Assets (ROA) and Return on Equity (ROE), while technical analysis is measured using the Moving Average (MA) and Relative Strength Index (RSI) indicators. The research employs a descriptive quantitative method with a multiple linear regression approach. The sample was selected through purposive sampling, resulting in 17 companies and 51 observational data points over a 3-year period. Data analysis techniques include classical assumption testing, regression analysis, and hypothesis testing both partially (t-test) and simultaneously (F-test). The results of this study are expected to provide valuable insights for investors regarding the importance of combining fundamental and technical analysis to improve the accuracy of return predictions and the effectiveness of investment decisions in the Indonesian capital market.